Thermal performance and comfort conditions analysis of a vernacular Palafitic timber building in Portuguese Coastline context - Fernandes, Jorge Emanuel Pereira (2020)
The palafitic timber constructions of the central Portuguese coastline are an example of the adaptation to site-specific conditions (climate and sand landscape morphodynamics) using the available endogenous resources. Thus, in a context of environmental awareness and climate change, it is relevant to understand their features/strategies and how they perform. This work analyses the energy performance and thermal condition evaluation of a vernacular timber building–palheiro–from Praia de Mira, through in situ measurements, subjective analysis and energy simulation provided by DesignBuilder/EnergyPlus. The results show a good or satisfactory thermal performance during most of the seasons by passive means only. Despite, it was not possible to guarantee thermal comfort conditions for the occupants during winter. In the energy performance analysis, five scenarios, with different external walls, were compared. In the two scenarios that satisfy the maximum U-value for the climate zone, the current conventional building had a slightly better performance on heating and cooling (less 1.1 and 1.4 kWh/m2, respectively) than the timber building. However, the difference between the two construction solutions is not substantial in the annual energy demand (2.5 kWh/m2, 7.3%), indicating that timber structures are suitable in this mild climate area.